Analysis of Gas Permeability Characteristics of Poly(Lactic Acid)/Poly(Butylene Succinate) Nanocomposites. (7th November 2012) - Bhatia, Amita; Gupta, Rahul K.; Bhattacharya, Sati N.; Choi, Hyoung Jin
Abstract : Gas permeability and morphological properties of nanocomposites prepared by the mixing of poly(lactic acid) (PLA), poly(butylene succinate) (PBS), and clay was investigated. While the composition of PLA and PBS polymers was fixed as 80% and 20% by weight, respectively, for all the nanocomposites, clay contents varied from 1 to 10 wt%. From the morphological studies using both wide angle X-ray diffraction and transmission electron microscopy, the nanocomposite having 1 wt% of clay was considered to have a mixed morphology of intercalated and delaminated structure, while some clusters or agglomerated particles were detected for nanocomposites having 3 and more than 3 wt% of clay content. However, the average particle size of the dispersed PBS phase was reduced significantly from 7  μ m to 30–40 nm with the addition of clay in the blend. The oxygen barrier property was improved significantly as compared to the water vapor. A model based on gas barrier property was used for the validation of the oxygen relative permeabilities of PLA/PBS/clay nanocomposites. PLA/PBS/clay nanocomposites validated the Bharadwaj model up to 3 wt% of clay contents only, while for nanocomposites of higher clay contents the Bharadwaj model was invalid due to the clusters and agglomerates formed.